The Portrayal of Urban Environmental Issues in Love, Lies and Indomee by Nuril Basri - Agustine, Siska Wahyu; Yulianto, Henrikus Joko (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Humans are dependent on nature, where humans need nature for their residence and for their daily needs. Humans should have a sense of care for nature as a form of reward. However, that statement is an illusion, because they are actually destroying nature. As a big city, Jakarta is a destination for migrants to improve their social or economic life. Uncontrolled population growth is one of the impacts of massive urbanization. As a result, social and ecological disparities become urban environmental issues that need to be considered by various parties. By using descriptive qualitative method, the researcher identified the phenomenon of urban environmental issues that occur in Jakarta, as the physical setting in Love, Lies and Indomee by Nuril Basri. Through this study, it is hoped that the readers will know the various kinds of urban environmental issues that occur in urban areas so that they will enthusiastically participate in the actions in protecting the environment.